Gypsies: The forgotten people of Turkey - (:unkn) unknown (My University, 2008)
As is the case in many European countries, the Gypsies of Turkey are currently unrecognised and misjudged by society. Victims of misunderstandings, discrimination in all areas (particularly socio-cultural and educational), they present a very negative image in the collective imagination. In addition, it is difficult to deal in any depth with the problems facing ethno-linguistic minorities in Turkey because there are only vague statistical estimates concerning their populations, since they are not officially recognised, given that the aim of Turkish cultural policy is assimilation, pure and simple. In order to join the EU Turkey will undoubtedly have to make an effort in certain areas, such as those connected with its socio-economic, cultural and educational level, the problem of Kurds and other minorities, and the issue of democracy and human rights. © UNESCO 2009.